2014
DOI: 10.1016/j.aller.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Confirmed penicillin allergy among patients receiving benzathine penicillin prophylaxis for acute rheumatic fever

Abstract: Our data suggest that the frequency of penicillin allergy is much lower than suspected among children on penicillin prophylaxis for ARF. Consequently, penicillin prophylaxis should not be given up without proper evaluation of drug allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Secondary prophylaxis for rheumatic fever can be safely administered in schools and settings other than hospital and health centers with few incidents of lifethreatening allergic reactions reported. [26][27][28][29] Of 17 641 penicillin injections administered among 535 children diagnosed with rheumatic fever in Turkey, there were only 11 reported allergies of which one was confirmed as a penicillin allergy. According to Grayson et al, in the New Zealand health system, the delivery of rheumatic fever prophylaxis at the community level (school, work, home, and clinic) resulted in high rates of adherence.…”
Section: Thompson Et Al Low Adherence To Secondary Prophylaxis Amongmentioning
confidence: 99%
“…Secondary prophylaxis for rheumatic fever can be safely administered in schools and settings other than hospital and health centers with few incidents of lifethreatening allergic reactions reported. [26][27][28][29] Of 17 641 penicillin injections administered among 535 children diagnosed with rheumatic fever in Turkey, there were only 11 reported allergies of which one was confirmed as a penicillin allergy. According to Grayson et al, in the New Zealand health system, the delivery of rheumatic fever prophylaxis at the community level (school, work, home, and clinic) resulted in high rates of adherence.…”
Section: Thompson Et Al Low Adherence To Secondary Prophylaxis Amongmentioning
confidence: 99%
“…Our early data also suggest that there is no need to perform routine penicillin-allergy testing prior to BPG administration in patients without a prior history of adverse reactions to penicillin.This position is supported by several large published studies that evaluated interventions with BPG in RHD patients, wherelarge numbers of BPG injections were administered withoutprior penicillin-allergy testing, 33 , 34 and reported the incidence of adverse reactions, including anaphylaxis, was exceedingly low. 36…”
Section: Discussionmentioning
confidence: 86%
“…A multinational study in 1991 that included 32 430 BPG injections in 1 790 patients estimated the risk of anaphylaxis to be exceedingly low, at approximately one in 10 000 injections, 33 and a 2014 retrospective study of BPG treatment in RF in Turkey found confirmed allergy in one of 535 patients (0.18% of 17 641 injections) but documented no anaphylactic reactions. 34 Three fatalities that were temporally related to BPG injection were reported from Zimbabwe more than 15 years ago, although clinical details were not well described and so it is not clear that drug allergy played a role. 35…”
Section: Discussionmentioning
confidence: 99%
“…There were no reported fatalities in this study. In 2014, a Turkish group reported suspected allergic reaction in 11 of 535 children, although following further testing all skin prick tests were negative and only one provocation test was positive 22. In Nigeria, an 11-year-old girl was successfully resuscitated following reported anaphylaxis after BPG for RHD; while in India a 40-year-old woman died 23 24.…”
Section: Resultsmentioning
confidence: 99%